Measurement of the CP-violating phase ϕs in B¯s0→J/ψπ+π− decays - R. Aaij; B. Adeva; M. Adinolfi; A. Affolder; Z. Ajaltouni; S. Akar; J. Albrecht; F. Alessio; M. Alexander; S. Ali; G. Alkhazov; P. Alvarez Cartelle; et al. (Physics Letters B, 2014)
The mixing-induced CP-violating phase ϕs in Bs0 and B¯s0 decays is measured using the J/ψπ+π− final state in data, taken from 3 fb−1 of integrated luminosity, collected with the LHCb detector in 7 and 8 TeV centre-of-mass pp collisions at the LHC. A time-dependent flavour-tagged amplitude analysis, allowing for direct CP violation, yields a value for the phase ϕs=70±68±8 mrad. This result is consistent with the Standard Model expectation and previous measurements.